Using management procedure gaps to enhance e-learning implementation in Africa - Awidi, I.; Cooper, Martin (Pergamon Press, 2015)
Management of Universities in Ghana have established good rationale for embracing e-learning as a new paradigm of educational delivery, and have demonstrated commitment by investing and building technology infrastructure necessary for e-learning. However, the approach to evaluate the institutional context as guide to successful e-learning implementation remains a problem. In the absence of standards for evaluation to guide the implementation process, this research investigated management approaches to facilitating e-learning implementation at a leading university in Ghana. To gain depth in understanding activities that support e-learning, a pilot survey was conducted. This was used to refine the research instruments. The survey questionnaire, interviews conducted, and institutional documents on e-learning activities provided depth of management practices that supports e-learning. The management procedures were then compared with some e-learning implementation best practice, and gaps were established. This paper has demonstrated that by using dimensional tools to establish procedure gaps in e-learning implementation, the short and long-term strategic plans will be put in perspective. The tool show how the university is moving from its current practices of educational delivery to e-learning or some blend. Universities with problems as discussed in this paper may achieve success by assembling an implementation team and a leader, determining the appropriate learning technology, clearly outlining the process of implementation and having an ongoing evaluation process to institutionalise the innovative e-learning approach. The policy and strategy document, showing the institutional position must include the pedagogical goals, infrastructure requirements, evaluation, collaboration with stakeholders, quality control, technical support, budget and funding and resource planning. The implementation of e-learning in an African University is examined. Management's goals and perceptions of the e-learning implementation are discussed. A set of dimensions are suggested to evaluate an e-learning implementation.